Respuesta :

Vankka

Answer: -9 = a(1 - 3)² + 3

Step-by-step explanation:

Vertex Form Equation:

y = a(x - h)² + k

vertex: (h, k) which means

h = 3

k = 3

because your vertex is (3, 3).

Your point is (1, -9) which is (x, y).

This means

x = 1

y = -9

Now, plug everything into your Vertex Form Equation:

-9 = a(1 - 3)² + 3

That’s your equation and final answer, but of course, if you need to, you can solve for a if you need to.

If a is positive, the parabola opens up. If a is negative, the parabola opens down.

Hope this helps!